Synthesis of isotopically labeled epothilones. (5th December 2013) - Ganesh, Thota; Brodie, Peggy J.; Banerjee, Abhijit; Bane, Susan; Kingston, David G. I.
<x xml:space="preserve">Abstract</x> The epothilones, including epothilones B and D, are macrocyclic lactones, which have potent cytotoxicities and promote the polymerization of tubulin to mictotubules by binding to and stabilizing the tubulin polymer. They have a very similar mechanism of action to paclitaxel (Taxol®). The determination of the microtubule‐binding conformation of the epothilones is an important piece of information in designing improved analogs for possible clinical use, and internuclear distance information that will assist the determination of this conformation can be obtained by rotational echo double resonance (REDOR) NMR studies of microtubule‐bound epothilones with appropriate stable isotope labels. Analogs of epothilone B and epothilone D with [2H3] and [19F] labels were prepared from an advanced precursor for potential use in REDOR NMR studies to determine internuclear distances in tubulin‐bound ligand. Copyright © 2013 John Wiley & Sons, Ltd.